2018
DOI: 10.2131/fts.5.127
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity study of poly-<i>trans</i>-[(2-carboxyethyl)germasesquioxane] (Ge-132) in F344 rats

Abstract: There were no adverse effects on survival rate, food consumption or hematology data, although diarrhea and bodyweight retardation were observed in the male and female 2.5% groups. Significant increases of kidney and adrenal weights were noted in both male and female 2.5% group. Macroscopically, dilatation of the cecum was observed in both male and female 2.5% group, and enlargement of the adrenals was observed in the male of 2.5% group. Significantly higher incidences of benign or malignant pheochromocytoma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In animal experiments, administration of 0.05% Ge-132 (40-70 mg/kg) for 30 days did not lead to signs of toxicity in mice, such as weight loss. In previous studies, the toxicity of Ge-132 has been investigated in various animal species (mouse, rat and dog), and its safety (extremely low toxicity) has been documented [60][61][62]. The LD50 was also determined in experiments using mice or rats, and its concentration was confirmed to be greater than 11 g/kg following oral administration [63].…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, administration of 0.05% Ge-132 (40-70 mg/kg) for 30 days did not lead to signs of toxicity in mice, such as weight loss. In previous studies, the toxicity of Ge-132 has been investigated in various animal species (mouse, rat and dog), and its safety (extremely low toxicity) has been documented [60][61][62]. The LD50 was also determined in experiments using mice or rats, and its concentration was confirmed to be greater than 11 g/kg following oral administration [63].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, daily administration of 5000 mg/kg Ge-132 did not cause any of the rats to die, and the maximum safe dose was estimated to be 1667 mg/kg [ 43 , 44 ]. Furthermore, it has been reported that oral Ge-132 is noncarcinogenic in mice and rats up to a concentration of 1,500 mg/kg/day [ 45 , 46 ]. A phase I study in Japan showed that in humans, Ge-132 is nontoxic up to a concentration of 75 mg/kg [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding concerns over the alleged high toxicity of Ge-132 (see Chapter 2), its toxicity [56][57][58] and possible carcinogenicity [81,82] have been studied many times over the past 10 years. The results of the research once again confirmed the complete safety of Ge-132.…”
Section: Germanium Sesquioxidesmentioning
confidence: 99%